Chloramphenicol levels in tiger shrimps (penaeus monodon) reared in a laboratory-controlled system and its effect on vibrio parahaemolyticus - Lim, Mui Hua (2012)
Chloramphenicol is a potent, broad-spectrum antibiotic suitable for the treatment of a variety of infectious diseases. It is banned in Europe and the United States because of the risk of aplastic anaemia and carcinogenic properties. According to the European Commission Decision 2001/699/EC and 2001/1705/EC certain fishery and aquaculture products imported for human consumption must be subjected to a test in order to ensure the absence of choramphenicol residues. This study was conducted to determine the level of chloramphenicol in tiger shrimps (Penaeus monodon) through its life cycle, the withdrawal period of tiger shrimps and to study the relationship between levels of chloramphenicol in the tissue of tiger shrimps and water samples. A commercial Enzyme-linked immunosorbent assay (ELISA) test was applied for the qualitative screening analysis in this experiment at a level corresponding to the European Union (EU) minimum required performance limit (MRPL) set for chloramphenicol analysis. The formulation which consisted of two different concentrations of Chloramphenicol: Treatment 1, Ti (50 mg/kg), and Treatment 2, T2 (75 mg/kg) were tested on tiger shrimps reared in experimental tanks. There was no significant differences (P>0.05) in water quality parameters such as pH, temperature, salinity and Dissolved Oxygen (DO). There was significant differences (P<0.05) between the levels of chloramphenicol in both treatments in the shrimp tissue and in the rearing water samples. However, the analysis of the level of chloramphenicol in the tissues in both treatment showed a similar trend of absorption. After termination of chloramphenicol in the feed. chloramphenicol residue was not detected at the eleventh and twelfth week for both water and tissue analysis. This study suggests that the withdrawal period of chloramphenicol in the shrimp tissue was two weeks. The antimicrobial susceptibility of V. parahaemolyticus isolated from aquaculture farms towards chloramphenicol and eight other antibiotics were also studied. V. parahaemolyticus was chosen as it was the most common bacteria isolated from the aquaculture ponds. The incidence of antimicrobial resistance pattern was compared in V. parahaemolyticus strains isolated from the hepatopancreas of tiger shrimps, water and sediment samples taken from the inlet, centre, outlet, reservoir and discharge section of four aquaculture farms in Kuching. In vitro resistance tests were performed by the standardized disk diffusion method on Mueller- Hinton agar (MHA). Three types of bacteria were isolated namely Vibrios, Chromobacterium violaceum and Hafnia alvei but vibrios were the most common bacteria. Among the Vibrios, the species commonly isolated was V. parahaemolyticus. A total of 140 V. parahaemolyticus strains isolated from the four different farms were examined for their antimicrobial resistance to nine commonly used antimicrobials: ampicillin, gentamicin, neomycin, cephalothin, tetracycline, nalidixic acid, kanamycin, chloramphenicol and streptomycin. In general, the most frequently encountered form of resistance in all the samples were resistance to ampicillin (100%), tetracycline (60%) and nalidixic acid (37.5%). On the other hand, all the strains from the samples were totally susceptible to gentamicin and chloramphenicol. Low levels of resistance of less than 30% were demonstrated in the other antimicrobial agents. The results in this study confirm that all V. parahaemolyticus strains were susceptible to chloramphenicol. However, the resistance towards ampicillin, tetracycline and rQlidixic acid suggest that the use of antimicrobials in tiger shrimps should be controlled to overcome future resistance problem.